PENGARUH PROFITABILITAS DAN KEBIJAKAN DIVIDEN TERHADAP HARGA SAHAM PADA PERUSAHAAN PROPERTY DAN REAL ESTATE - Ardhyansyah, Vingky Riswanto; Praptoyo, Sugeng (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya, 2022)
This research aimed to examine the effect of profitability which was referred to as Return on Equity, and dividend policy which was referred to as the Dividend Payout Ratio on the stock price of property companies and Real Estate companies that were listed on Indonesia Stock Exchange 2017-2020. The research result concluded that Return on Equity had an insignificant effect on the stock price. It happened as companies' profit was not the only indicator of ROE. ROE had only viewed companies’ performance in getting some profits with owners’ investment. It lacked showing companies’ development and their prospect; so, the investors did not consider ROE as an investment consideration. In contrast, the Dividend Payout Ratio had a significant effect on the stock price. This meant investors preferred to have little share dividend since paid tax followed by the accepted dividend.